Impact of hypokalemia on peritonitis in peritoneal dialysis patients: a systematic review. Issue 1 (December 2017) - Nakai, Kentaro; Saito, Kei; Fujii, Hideki; Nishi, Shinichi
Abstracts Background Hypokalemia is a common electrolyte disorder in peritoneal dialysis patients. Some studies showed the association of serum potassium levels with all-cause and cardiovascular mortality and infection. This review aims to clarify the relationship of hypokalemia and peritonitis in peritoneal dialysis. Methods The MEDLINE and Cochrane Library databases were searched for articles published from 1990 to May 2016. The following search terms were used: hypokal(a)emia, potassium, peritoneal dialysis, peritonitis, and infection. Additional studies were identified by hand searching through references and using the MEDLINE-related articles option. Two investigators independently selected studies using predefined criteria and assessed each study's quality using the Newcastle-Ottawa Quality Assessment Scale. Results A total of 159 abstracts were identified and 6 trials were included in the systematic review (n = 3613). One national prospective study and two retrospective single-center studies indicated that hypokalemia increases the risk of peritonitis, whether two single-center studies indicated otherwise. One case-control study indicated that lower potassium level was associated with a poor therapeutic outcome in peritonitis. Conclusion Convincing clinical trial data are unavailable to show the association of hypokalemia with peritonitis in peritoneal dialysis patients, and we need to clarify whether the therapeutic intervention to normalize serum potassium levels decreases the risk of peritonitis and infection-related mortality in peritoneal dialysis patients.